(3 + 1)-Dimensional commensurately modulated structure and photoluminescence properties of diborate KSbOB2O5. Issue 13 (5th March 2015) - Zhao, Dan; Zhang, Rong-Hua; Li, Fei-Fei; Yang, Juan; Liu, Bing-Guo; Fan, Yun-Chang
Abstract : This work reports the commensurately modulated structure of KSbOB2 O5 using superspace formalism for aperiodic structures considering a modulation vector q = 5/12 b *. Abstract : Single-crystal diborate KSbOB2 O5 has been prepared under a high temperature molten-salt method and its structure has been determined by single crystal X-ray diffraction analysis. The diffraction pattern shows strong main reflections and weak satellite reflections, clearly indicating a modulated structure. Using the four-dimensional superspace formalism for aperiodic structures, its reflections could be indexed as orthorhombic superspace group Pmn 21 (0 β 0) s 00 with the modulation vector q = 5/12 b *, and then the structure solution and refinement reached a final commensurately modulated model that was refined extremely well and did not show any unusual features. On the other hand, the powder sample of KSbOB2 O5 was synthesized by the high-temperature solid-state reaction method, and the powder X-ray diffraction pattern fits very well with the simulated from the single-crystal data. In addition, photoluminescence properties of diborate KSbOB2 O5 activated by 4.5 mol% Dy 3+ have been studied, indicating an extraordinary phenomenon that the red emission at around 635 nm ( 4 F9/2 → 6 H11/2 ) is much stronger than the yellow emission at around 581 nm ( 4 F9/2 → 6 H13/2 ).